Indoleamine 2,3-Dioxygenase 1 Inhibitor-Loaded Nanosheets Enhance CAR-T Cell Function in Esophageal Squamous Cell Carcinoma - Shao, Jingwen; Hou, Lin; Liu, Jinyan; Liu, Yulin; Ning, Jie; Zhao, Qitai; Zhang, Yi (Frontiers in Immunology, 2021)
In chimeric antigen receptor (CAR)-T cell therapy, the role and mechanism of indoleamine 2, 3 dioxygenase 1 (IDO1) in enhancing antitumor immunity require further study. IDO1 is one of the most important immunosuppressive proteins in esophageal squamous cell carcinoma (ESCC). However, the IDO1 inhibitor, epacadostat, has failed in phase III clinical trials; its limited capacity to inhibit IDO1 expression at tumor sites was regarded as a key reason for clinical failure. In this study, we innovatively loaded the IDO1 inhibitor into hyaluronic acid-modified nanomaterial graphene oxide (HA-GO) and explored its potential efficacy in combination with CAR-T cell therapy. We found that inhibition of the antitumor effect of CAR-T cells in ESCC was dependent on the IDO1 metabolite kynurenine. Kynurenine could suppress CAR-T cell cytokine secretion and cytotoxic activity. Inhibiting IDO1 activity significantly enhanced the antitumor effect of CAR-T cells in vitro and in vivo. Our findings suggested that IDO1 inhibitor-loaded nanosheets could enhance the antitumor effect of CAR-T cells compared with free IDO1 inhibitor. Nanosheet-loading therefore provides a promising approach for improving CAR-T cell therapeutic efficacy in solid tumors.